On berm design of Icelandic-type breakwaters (case study: Sirevåg berm breakwater). Issue 1 (23rd March 2022) - Ehsani, Majid; Moghim, Mohammad Navid; Shafieefar, Mehdi
Abstract : An experimental model of an Icelandic-berm breakwater has been set up in the hydraulic laboratory of Tarbiat Modares University using irregular waves. Experimental model tests have been carried out using a wide range of sea-state conditions and geometrical parameters to measure different parameters, such as the eroded area ( A e ), the berm recession (Rec) and the depth of the intersection point of initial and reshaped profiles ( h f ). A stability formula is proposed to establish the relationship between the damage parameter of the Icelandic-berm breakwater ( S d ) and the non-dimensional form of Rec and h f . The application of the given formula for estimating the berm recession in the phenomenon and practical cases was evaluated employing the Sirevåg berm breakwater. The results of the evaluation highlight the appropriate estimation of berm recession. Moreover, some recommendations are suggested to consider berm parameters, such as the berm width, the berm elevation from still water level and the height of class I stones, as an Icelandic-type berm breakwater design criterion for future engineers. Eventually, taking all the proposed formulae and recommendations into consideration, a design tool for engineers in berm design of berm breakwaters has been provided.